2021
DOI: 10.31729/jnma.7004
|View full text |Cite
|
Sign up to set email alerts
|

The Yentl Syndrome: A Case Report

Abstract: Cardiovascular disease, including ischemic heart disease, is one of the most common causes of death and disability in both sexes. The traditional concept of ischemic heart disease as a “man’s disease” is debunked. Yentl syndrome is used to describe the underdiagnosis of ischemic heart disease in females and its associated effects. This article reports a 48-year-old female presented to the emergency department with acute epigastric discomfort. Her initial diagnostic tests did not reveal any abnormalities, and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
1
0
Order By: Relevance
“…Craniofacial pain can be the sole symptom in up to 6% of patients with AMI [ 6 ]. Women need special mention as they often present with atypical symptoms, and a high index of suspicion is required [ 7 ]. It can lead to delayed diagnosis, suboptimal treatment, and detrimental outcomes [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Craniofacial pain can be the sole symptom in up to 6% of patients with AMI [ 6 ]. Women need special mention as they often present with atypical symptoms, and a high index of suspicion is required [ 7 ]. It can lead to delayed diagnosis, suboptimal treatment, and detrimental outcomes [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another study found women were less likely to be admitted to the hospital for chest pain than men [13]. The Yentl Syndrome, based on a case study, hypothesizes when women present like men with CHD they are more likely to be treated like men and because women do not typically present the same symptoms they are more likely to be undertreated [14]. Another study found women were less likely to survive an acute myocardial infarction when treated by a male cardiologist [15].…”
Section: Discussionmentioning
confidence: 99%